The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.seppur.2014.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of chemical conditioning with inorganic polymer flocculants on soluble extracellular polymeric substances in relation to the sludge dewaterability

Abstract: a b s t r a c tGenerally, sludge conditioned with inorganic coagulants exhibits rigid structure and is suitable for high pressure dewatering process. Sludge flocs possess multilayered structure, and the sludge dewaterability is mainly dependent on the properties of soluble extracellular polymeric substances (SEPS). However, few studies have focused on influence of chemical conditioning on the characteristics of SEPS. In this study, the surplus sludge obtained from wastewater treatment plant (WWTP) was conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 40 publications
2
45
1
Order By: Relevance
“…It reached the minimum of 86.31 wt% when the dosage of CaO 2 was 20 mg/gTSS and the SRF was 1.28 Â 10 13 m/kg. According to the value of SRF, sludge can be classified into poor dewaterability (>1 Â 10 13 m/kg), medium dewaterability, (0.5e0.9 Â 10 13 m/kg) and good dewaterability (<0.4 Â 10 13 m/kg) (Zhang et al, 2014). By comparison, although addition of CaO 2 can improve sludge dewatering performance, the minimum SRF value can not reach the sludge with good dewaterability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It reached the minimum of 86.31 wt% when the dosage of CaO 2 was 20 mg/gTSS and the SRF was 1.28 Â 10 13 m/kg. According to the value of SRF, sludge can be classified into poor dewaterability (>1 Â 10 13 m/kg), medium dewaterability, (0.5e0.9 Â 10 13 m/kg) and good dewaterability (<0.4 Â 10 13 m/kg) (Zhang et al, 2014). By comparison, although addition of CaO 2 can improve sludge dewatering performance, the minimum SRF value can not reach the sludge with good dewaterability.…”
Section: Resultsmentioning
confidence: 99%
“…For example, addition of inorganic or organic flocculants can agglomerate fine sludge colloids to form large flocs through charge neutralization and bridging, which can be more easily separated from the water (Niu et al, 2013;Zhang et al, 2014). EPS fraction in activated sludge was highly hydrated, and the traditional chemical flocculants was ineffective to destroy EPS structure and convert bound water into free water (Neyens et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(Zhang et al, 2015b). Many studies have demonstrated that sludge filtration property was mainly dependent on properties of soluble EPS fraction, and the high content of protein in soluble EPS was always detrimental to sludge filterability (Zhang et al, 2014b(Zhang et al, , 2015c(Zhang et al, , 2015d. In addition, reduction of soluble EPS concentration contributed to improvement of sludge filterability, it was obvious that TSC 0.5 was more effective in removal of soluble EPS fraction.…”
Section: Fig 4 Effects Of Tscs Dosages On Concentrations Of Differementioning
confidence: 99%
“…Addition of traditional chemical conditioners (inorganic salt coagulants and organic polymers) can agglomerate fine sludge colloids to form large flocs through charge neutralization and bridging, which can be more easily separated from the water (Niu et al, 2013;Zhang et al, 2014a). TiCl 4 is novel environmentally friendly inorganic coagulants and has attracted much attention in water and wastewater treatment (Shon et al, 2007;Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…5 can see that the TB-EPS concentrations conditioned by Al 13 and PAC 2.5 increased again comparing to other aluminum salt coagulants, this also indicated that Al b and Al c showed better performance in compressing EPS structure than Al a , which made SEPS and LB-EPS transfer into TB-EPS, so TP-EPS conditioned by Al 13 and PAC 2.5 increased when SEPS and LB-EPS concentration conditioned by Al 13 and PAC 2.5 decrease, so their TB-EPS concentration was increased. Many studies have demonstrated that sludge filtration property was mainly dependent on properties of SEPS fraction, and the high content of protein in SEPS was always detrimental to sludge filterability (Zhang et al, 2014a(Zhang et al, , 2014b(Zhang et al, , 2015b. In addition, reduction of SEPS concentration contributed to improvement of sludge filterability, it was obvious that PAC with high alkalinity and Al 13 were more effective in removal of SEPS.…”
Section: The Influence Of Hydroxyl Aluminum Conditioning With Differementioning
confidence: 99%